Audit partner identification, matching, and the labor market for audit talent - Deng, Mingcherng; Kim, Eunhee; Ye, Minlei (Contemporary Accounting Research, 2023)
Abstract Conventional wisdom suggests that audit engagement partner name disclosure benefits investors by informing them about the partners' performance. However, such public disclosure of the identity of the audit partners may also intensify competition for audit talent in the labor market. To examine the economic consequences of audit partner identification, we build a two‐period model in which an audit firm matches partners to clients. The audit partner identification broadens a partner's outside options in the labor market, making talent retention more costly. If the talent‐retention cost is substantial, audit partner identification may cause an audit firm to adjust its partners' compensation packages and mismatch the partners and clients, which may lead to lower audit quality. Overall, we identify unintended consequences of audit partner identification by examining its impact on the audit labor market, and we provide economic reasons for the mixed empirical findings.